Moderating effect job satisfaction on the determinants of herzberg’s two-factor theory towards job performance among customer service representative at in-house call center in banking sector, Klang valley / Noorlaila Hj. Yunus and Nor Hashimah Kamal. - Yunus (Hj.), Noorlaila; Kamal, Nor Hashimah (Faculty of Business and Management and UiTM Press Universiti Teknologi MARA, Malaysia., 2017)
The study was aimed to determine the relationship between Herzberg’s Two Factor Theory towards job performance and the moderating effect of job satisfaction toward the relationship between Herzberg’s Two-Factor Theory and job performance among customer service representative at in-house call centre in banking sector, Klang Valley. The independent variable is focus on five factors, which are salary and wages, working condition, recognition, supervision and work life balance, while dependent variable is job performance and the moderating variable is job satisfaction. In order to know more on the relatedness between those variables towards customer service representative in organization, this research was conducted to access the relationship between Herzberg’s Two-Factor Theory towards job performance and the moderating effect of job satisfaction at inhouse call centre in banking sector, Klang Valley.